Hot Tensile Deformation Behavior of Mg-4Li-1Al-0.5Y Alloy - Yang, Ting; Li, Zhuohua; Wang, Jinhui; Jin, Peipeng (Frontiers in Materials, 2021)
The microstructure evolution and deformation mechanism of the as-extruded-annealed Mg-4Li-1Al-0.5Y alloy (denoted as LAY410) were investigated during hot tensile deformation at the temperatures between 150℃ and 300℃ with strains from 8×10-5 s-1 to 1.6×10-3 s-1. The results show that when the strain rate decrease and/or the deformation temperature increase, the peak stress of the alloy gradually decreases, and the elongations to fracture gradually increases. The true stress-strain curves show typical dynamic recrystallization (DRX) softening characteristics. It is observed that the microstructure in the magnesium (Mg) alloy deformed at 150°C are mainly composed of the deformed grains and a few the recrystallized grains. The microstructures in the Mg alloy deformed at 200°C are consisted of substructures and the slightly increasing number of dynamic recrystallized grains. When the deformation temperature reaches 250°C, the number of recrystallized grains increases significantly, and the microstructures are dominated by recrystallized grains. Moreover, through theoretical calculation and result analysis, the activation energy was about 99.3 kJ/mol, and the hot tensile deformation mechanism was the alternate coordinated deformation mechanism among grain boundary slip (GBS), intragranular slip and DRX.